Understanding Associative Learning Through Higher-Order Conditioning - Gostolupce, Dilara; Lay, Belinda P. P.; Maes, Etienne J. P.; Iordanova, Mihaela D. (Frontiers in Behavioral Neuroscience, 2022)
Associative learning is often considered to require the physical presence of stimuli in the environment in order for them to be linked. This, however, is not a necessary condition for learning. Indeed, associative relationships can form between events that are never directly paired. That is, associative learning can occur by integrating information across different phases of training. Higher-order conditioning provides evidence for such learning through two deceptively similar designs - sensory preconditioning and second-order conditioning. In this review, we detail the procedures and factors that influence learning in these designs, describe the associative relationships that can be acquired, and argue for the importance of this knowledge in studying the brain function.